Persepsi Mahasiswa Akuntansi Mengenai Penghargaan Finansial Terhadap Pilihan Karirnya Sebagai Akuntan Publik - Danna Solihin (RJABM (Research Journal of Accounting and Business Management), 2017)
Career is an entire working position held during the life cycle of a person's job. Factors that influence career choice are intelligence ability, interest, personality and motivation. One form of motivation is financial reward. This study indicates a relevancy between perception of accounting student about financial reward and career choice as public accountant. Perception of accounting student about financial reward is results obtained as a contracting of the work that has been fundamentally believed for most companies as the main attraction to give satisfaction to its employee. Public Accountant is a career who gives good reward financial and varying work experience